The attitude of the police officers of the RS Ministry of Interior Affairs to alcohol and drug addicts - Milovanović Anatolij (Trendovi u Poslovanju)
The main problem in this research paper is the situation in which the police in Republika Srpska performing their duties and tasks apply repressive measures against persons dependent on alcohol and narcotics. A special part of this problem is the intention of these persons to use weapons. On the basis of this, the subject of the research was formulated: "The attitude of the police officers of the Ministry of Interior Affairs of Republika Srpska to alcohol and drug addicts". The aim of the research is to determine the required level of repressive measures of the police against the stated persons. If police officers face people addicted to alcohol or narcotics during the course of their tasks, special repressive measures are required, that is, if alcohol and drug addicts show resistance during police intervention, then the police authorizations must be larger. A survey of members of the Ministry of Interior Affairs of Republika Srpska was conducted, that is, an assessment was made of the intensity of their attitudes and beliefs related to the intention of the alcoholics and addicts of psychoactive substances to use weapons against the police. The scientific contribution in this paper is the analysis of empirical research, which is the starting point in the adoption of new legal regulations in the application of repressive measures against these persons.